Information Adequacy in Histopathology Request Forms: A Milestone in Making a Communication Bridge Between Confusion and Clarity in Medical Diagnosis - Fariba ABBASI,; Yasaman ASGHARI; Zahra NIAZKHANI, (Türk Patoloji Dergisi, 2023)

(untitled)
Objective: Information contained in request forms for histopathological examinations plays a critical role in the microscopic interpretation of tissue changes. Despite its importance, studies have shown inadequacies in the information communicated by clinicians. This study aimed to determine how well the necessary information is provided on the histopathology request forms and to compare its variability among different departments of a hospital.